Formação de valores e identidade na adolescência: uma experiência - Barreiro, Iraide Marques de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
We report the work developed in two public schools of Assis involving, on the one hand, students from the fifth to the twelfth grade and, on the other hand, work developed by 3rd year Psychology students during a teacher training practice held under the supervision of a professor of Psychology. At college level, the content was developed by means of reflexive action linked to educational practices which foster changes, acquisition of values and attitudes by elementary and high school students. The syllabus for that course was worked up taking into consideration the needs felt by those students in broach topics such as respect, justice, violence, solidarity, family friendship, adolescency, sexuality, dating, pregnancy, abortion, drugs, and STDs. Thematic Workshops were used as one of the strategies to develop the syllabus content and the courses at issue were taught by two college training students in each class, during a one-hour class a week. At the end of the course, the college students have managed to master the issues listed above, showing more confidence and propriety.

Relata-se a experiência do trabalho desenvolvido em duas escolas estaduais na cidade de Assis, com alunos da 5a série ao colegial, como parte das atividades de estágio junto à disciplina de Prática de Ensino de Psicologia, ministrada aos alunos do 3o ano do curso de Psicologia. Na forma de curso, o conteúdo foi desenvolvido por meio de ações reflexivas vinculadas a práticas educativas favorecedoras de mudanças e da aquisição de novos valores e atitudes entre os alunos das escolas. O programa foi montado a partir das demandas apresentadas no início do ano pelos alunos, tais como: respeito, justiça, violência, solidariedade, família, amizade, adolescência, sexualidade, namoro, gravidez, aborto, violência, drogas e DSTs. Valendo-se de Oficinas Temáticas, como uma das estratégias para trabalhar os conteúdos, o curso foi ministrado por dois estagiários em cada classe, durante uma hora aula semanal, no decorrer do ano. Ao término do curso, os alunos têm se expressado com maior tranqüilidade e propriedade sobre os temas tratados.
Acquisition of values and identity by teenagers: an experience
Keywords: Acquisition of values; Attitudes; Identity; Adolescency; Humanas; Educação; Formação de valores; Atitudes; Identidade; Adolescência